A new approach for estimating internal stability of reinforced soil structures. Issue 4 (21st April 2017) - Weerasekara, L.; Hall, B.; Wijewickreme, D.
Abstract : The current practice for designing reinforced soil structures involves the use of empirical or semi-empirical methods to estimate the maximum reinforcement loads using different variants of tributary area method. As the soil–reinforcement interaction is not explicitly captured in these methods, a number of limitations exist in estimating the maximum reinforcement load and pullout resistance. This paper presents a new method called the soil–reinforcement interaction method to assess the internal stability of reinforced soil structures. As a part of its derivation, a more refined interface friction model was developed that accounts for the increased friction from soil dilation and subsequent reduction in friction with displacement. By combining the interface friction model and reinforcement stiffness, an analytical model was developed to relate the displacement, strain, force, and mobilized frictional length for a given reinforcement. Using this model, an approach was developed to assess the internal stability of reinforced soil structures. The method allows estimation of the factor of safety against internal failure by considering the soil–reinforcement interaction and boundary conditions. To demonstrate the applicability of this method, several reported pullout tests and three full-scale reinforced walls are modeled.